Roads on a downhill? Trends in EU infrastructure investment - Timo Välilä; Tomasz Kozluk; Aaron Mehrotra (EIB Papers, 2005)
This paper describes long-term trends in public investment and analyses their causes and consequences. This has been undertaken separately for the EU-15 and the new member countries in Central and Eastern Europe. In addition, it assesses the significance of infrastructure finance through public-private partnerships, which are often portrayed as a substitute for traditional public procurement of infrastructure. The conclusion that emerges is that while public investment has been trending down in non-cohesion countries and while public-private partnerships are gaining popularity, the quantitative significance of these developments should not be exaggerated.
Keywords: 330; Infrastrukturinvestition; Unternehmensfinanzierung; Public-Private Partnership; EU-Staaten